ANALISIS FAKTOR YANG BERHUBUNGAN TERHADAP KEPATUHAN PEMAKAIAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA PROYEK X BSD TAHUN 2021 - Lily Pavitasari Qauliyah (2021)
The absence of the use of Personal Protective Equipment (PPE) can increase the occurrence of work accidents. Compliance with the use of PPE can be influenced by three factors including predisposing factors, enabling factors, and reinforcing factors. These factors can cause work accidents in construction projects. Data obtained from project X, still found work accidents, which were allegedly due to workers' disobedience in the use of PPE.The purpose of this study was to analyze the compliance of workers through age, education, working period, knowledge, training, and supervision of the use of PPE for workers in Project X BSD. This study was a quantitative analytic study with a cross-sectional design with Chi-Square test. The research sample was 133 workers by purposive sampling. The results of this study showed that 58.6% of workers complied with wearing PPE. The results of statistical analysis showed that knowledge (P-value = 0.002), training (P-value = 0.008), and supervision (P-value 0.012) had a significant relationship with compliance with the use of PPE. Meanwhile, age (P-value = 0.542), education (P-value = 1,000), and working period (P-value = 0.216) did not have a significant relationship with compliance with the use of PPE. So, from the existing variables only knowledge, training, and supervision have a relationship with compliance with the use of PPE. The company is advised to increase the knowledge of workers by carrying out regular training and supervision in the workplace so that project workers comply with wearing PPE.